Relative contribution of arms and legs through repetitive assisted sit-to-stand motion in individuals with incomplete spinal cord injury / Musfirah Abd Aziz - Musfirah, Abd Aziz (2020)
Sit-To-Stand (SitTS) exercise is one of important prerequisites to achieve some functional independence goals in everyday life especially for individuals undergoing rehabilitation In general, the execution of SitTS in spinal cord injury (SCI) patients involves motor function in both upper and lower extremities. The use of arm support in particular is a very significant element while executing SitTS movement for SCI population. In addition, application of functional electrical stimulation (FES) onto the quadriceps muscles is one of the prescribed management for incomplete SCI to improve muscle action for simple lower limb movements. However, the relative contribution of upper and lower extremities during SitTS has not been studied thoroughly. Therefore, the objective of this study is to determine the contribution of arm and leg during repetitive SitTS in incomplete SCI participants with and without FES. Two motor incomplete SCI participants performed repetitive SitTS-to fatigue exercise challenge. Three sets of SitTS test were completed with five-minute resting period were allocated in between set, with mechanomyography (MMG) sensors attached over the belly of the quadriceps muscles bilaterally. A total of 399 and 463 SitTS trials were completed without and with FES respectively by both participants. A SitTS cycle can be divided into three phases; Phase 1 (Preparation to stand), Phase 2 (Seat-off) and Phase 3 (Initiation of hip extension) which contributed to 23 ± 7%, 16 ± 4% and 61 ± 6% of the SitTS cycle respectively. Overall, the mean time to complete each FES-SitTS cycle between early trials for each set was identified to be significantly shorter compared to the final trials in each set (p<0.0005). The contribution of leg and arm during SitTS movement varied in different participants based on their legs Medical Research Council (MRC) muscle grade. During early Phase iv 2 of voluntary and assisted SitTS, in terms of percentage of total participants body weight, both participants showed higher arms percentage contribution compared to their legs. Meanwhile throughout the end of Phase 3 in the SitTS activity, the percentage of arms contribution increased only for Participant 1 due to his right leg condition that was weak. For Participant 2, the percentage of arms contribution decreased as the contribution of leg percentage increased. For both conditions, there were significant average differences in the percentage of total body weight contribution between early Phase 2 and the end of Phase 3 for arm (p<0.001) and leg (p<0.001). This study highlighted the relative contribution of arm support in SitTS activity in two individuals with motor incomplete SCI. The finding might serve as a reference for SCI individuals to do a safe SitTS protocol hence future rehabilitative SitTS exercise where strength training of arm and leg can be emphasised.